Caracterização elétrica de eletrólitos baseados em céria Nano e microcristalinos para pilhas a combustível - Lapa, Camila Maria (Universidade Federal de São Carlos, 2008)
Fuel cells are considered the most promising way for generating electrical energy in a near future. The economic fuel cells viability is directly related to the reduction of its operating temperature which is related to the properties of the electrolyte. In this work ceramic nanopowders of Ce0.8Y0.2O1.9 e Ce0.8Gd0.2O1.9 obtained by chemical synthesis were sintered through two-step sintering to obtain dense bodies with submicormetric grain size, in order to improve the grain boundary electrical conductivity of ceria-based electrolytes. Grain and grian boundary conductivities are dependent on grain size besides sintering schedule. The formation of secondary phases indicates that the improvement in grain boundary conductivity is related to the microdomains dynamics in microstructure. Ga2O3 addition was not effective in the densification of Ce0.8Y0.2O1.9 e Ce0.8Gd0.2O1.9 ceramics and it was deleterious to grain boundary conductivity, although it improved grain conductivity comparing to Ga2O3 free samples. An alternative to improve the electrical conductivity of ceria-based electrolytes is the formation of nanometric doped ceria amorphous carbonate composites. The composites were characterized and the components were set in different arrangements to evaluate the existence of interfacial effedt between the phases. The electrical characterization of these sets does not indicate the existence of this interfacial effect.
Electrical characterization of nano and microcrystalline ceria based electrolyte for fuel cells
Keywords: Cerâmica eletrônica; Célula à combustível (CAC); Nanotecnologia; Pó de cerâmica - síntese; Sinterização; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA